Ultraviolet-B radiation stress triggers reactive oxygen species and regulates the antioxidant defense and photosynthesis systems of intertidal red algae Neoporphyra haitanensis - Song Xue; Yu Zang; Jun Chen; Shuai Shang; Lihua Gao; Xuexi Tang (Frontiers in Marine Science, 2022)
The enhancement of harmful ultraviolet-B (UV-B, 280–320 nm wavelength) radiation is a serious problem generally faced by photosynthetic organisms. Previous studies have reported that the currently increasing level of UV-B radiation received on earth can promote the formation of reactive oxygen species (ROS) by altering the antioxidant defense system or by hampering of photosynthesis system of plants. However, the relationship between the UV-B-induced ROS production, antioxidant capacity, and photosynthetic performance in macroalgae remains unclear. In this study, the regulation of the antioxidant system and photosynthetic activity by ROS triggered by UV-B radiation were investigated in an intertidal seaweed, Neoporphyra haitanensis . The contents of hydrogen peroxide and malondialdehyde increased with enhanced UV-B radiation, indicating N. haitanensis experienced oxidative stress. Increased activities of antioxidant enzymes showed a positive response of enzymatic antioxidants to maintain the balance of ROS under low UV-B conditions. Likewise, an accumulation of non-enzymatic antioxidants occurred and glutathione redox status was maintained at a high level, suggesting that the ascorbate–glutathione cycle played an indispensable role in detoxifying ROS. Nevertheless, high UV-B radiation markedly inhibited the efficiency of the enzymatic and non-enzymatic antioxidants, causing oxidative damage and a depression of photosynthesis. The addition of ROS scavengers alleviated the increased oxidation level caused by UV-B radiation, implying that oxidative damage under UV-B condition was ascribed to accumulated ROS. The activation of the antioxidant defense system was also modulated by ROS. Additionally, the decreased photosynthetic activities induced by enhanced UV-B radiation were reversed by ROS scavengers, indicating that ROS-mediated oxidative damage caused by UV-B radiation is one of the important causes of photo-inhibitory damage in N. haitanensis . Overall, these results shed some light on the close relationship between UV-B-induced ROS production, the antioxidant defense system, and photosynthetic performance in macroalgae, which helps to reveal their survival strategies for adapting to highly variable marine intertidal environments.